The Interrelationship of Nation Building, Reconciliation and Guarantees of Non-Recurrence (or Non-Repetition) of Human Rights Violations Using the South African Transition as an Illustration: how Victim Rights and Needs Can Be Better Achieved = La interrelación entre la construcción de la nación, la reconciliación y las garantías de no reincidencia (o no repetición) de las violaciones de los derechos humanos a la luz del ejemplo de la transición en Sudáfrica : cómo mejorar la satisfacción de los derechos y necesidades de las víctimas - Sarkin, Jeremy (Revista de victimología, 2017)
Dealing with past human rights violations is now an agenda item in many countries. In such states where there has been division and instability, and processes to attain greater democracy and human rights are successful, at times, and over time, human rights violations re-emerge to a lesser or greater extent than before. Thus, in a number of cases problems resurface, and there is a slide backwards in the human rights culture that has developed. In this context, while reconciliation practices have been extensively examined, with much focus on victims’ need for truth, reparations and justice, relatively little academic or other attention has been paid to how nation-building and reconciliation processes can promote guarantees of non-repetition or non-recurrence of human rights abuses. These are important needs of victims. They have been insufficiently studied and are inadequately understood. The South African model is used to illustrate and amplify the issues. This article examines South Africa’s transition to determine how nation building, reconciliation and promotion of democracy advance guarantees of non-repetition or non-recurrence of human rights abuses and how they are connected and overlap with a range of issues. Issues discussed including how democratisation, including the drafting of a constitution, containing various rights and protections, can assist in this regard. Also focused on is the role of the Truth and Reconciliation Commission.